Quantitative elastography associated with endoscopic ultrasound for the diagnosis of chronic pancreatitis - Iglesias-Garcia, Julio; Domínguez-Muñoz, J. Enrique; Castiñeira-Alvariño, Marga; Luaces-Regueira, Maria; Lariño-Noia, Jose (Endoscopy, 2013)
Background and study aims: Endoscopic ultrasonography (EUS) has become the method of choice for the diagnosis of chronic pancreatitis in clinical practice. However, the criteria allowing the specific diagnosis of the disease, mainly at non-advanced stages, are still under debate. Analysis of tissue stiffness by quantitative EUS–elastography may provide additional relevant information in this setting. The aim of this study was to evaluate the information provided by quantitative EUS–elastography for the diagnosis of chronic pancreatitis.Patients and methods: A prospective, consecutive, 1-year study was designed, and included patients who underwent EUS for epigastric pain syndrome or known chronic pancreatitis. EUS–elastography was performed using radial Pentax EUS and Hitachi EUB900. The strain ratio was measured in the head, body, and tail of the pancreas, and the elastographic result was the mean of these three values. EUS criteria of chronic pancreatitis and the Rosemont classification were also evaluated. Data were analyzed by analysis of variance and linear regression; diagnostic accuracy was based on the receiver operating characteristic (ROC) curve analysis.Results: A total of 191 patients (mean age 52 years, range 21 – 85; 103 male) were included; 92 (48.2 %) of them were finally diagnosed with chronic pancreatitis. A highly significant direct linear correlation was found between the number of EUS criteria of chronic pancreatitis and the strain ratio (r = 0.813; P < 0.0001). The area under the ROC curve was 0.949 (95 % confidence interval 0.916 – 0.982) and the accuracy of EUS–elastography for diagnosing chronic pancreatitis was 91.1 % (cut-off strain ratio of 2.25). The strain ratio varied significantly in different Rosemont classification groups (P < 0.001).Conclusions: EUS–elastography was an accurate tool for the diagnosis of chronic pancreatitis and provided relevant and objective information to support EUS findings.